World Economic Outlook, October 2000 : Focus on Transition Economies. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2001)
The World Economic Outlook, published twice a year in English, French, Spanish, and Arabic, presents IMF staff economists' analyses of global economic developments during the near and medium term. Chapters give an overview of the world economy; consider issues affecting industrial countries, developing countries, and economies in transition to market; and address topics of pressing current interest. Annexes, boxes, charts, and an extensive statistical appendix augment the text.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet